The deposition and light absorption property of carbonaceous matter in the Himalayas and Tibetan Plateau - Yan, Fangping (Lappeenranta-Lahti University of Technology LUT, 2020)
The Himalayas and Tibetan Plateau (HTP), known as the ―Third Pole‖ and ―world roof‖, contains the largest amount of glaciers outside the Arctic and Antarctic. Carbonaceous matter, mainly including black carbon (BC) and organic carbon (OC), plays important role in climate forcing of the atmosphere and glacier retreat after its deposition on the glacier surface in the HTP. With the rapid climate change and glacier retreat, the study on carbonaceous matter in the HTP has become a hotspot in recent few decades. Although a series of studies on carbonaceous matter in the atmosphere and glacier regions of the HTP have been conducted, large uncertainties still existed. Therefore, this work was carried out to first discuss the uncertainties in previous studies and adjust the reported data of carbonaceous matter in the HTP. Then in-situ observations were conducted at three remote stations and an urban site in the HTP to comprehensively investigate reliable concentrations and deposition rates of carbonaceous mater in precipitation, and the atmospheric dry deposition rates of particulate carbon. Meanwhile, the scavenging mechanisms of carbonaceous matter in the atmosphere were discussed. Furthermore, the OC, especially the water-insoluble fraction, exerts strong light absorption particularly in the UV wavelength rage. However, the methods in previous studies to investigate the light absorption of this water-insoluble organic carbon (WIOC) have large uncertainties. To accurately estimate its light absorption, the uncertainties in previous methods to extract WIOC with methanol were discussed, and a new method was developed in this work. The results in this work indicated that the previously reported concentrations of the atmospheric BC and OC were overestimated due to the influence of inorganic carbon (e.g. carbonate) in mineral dust because of the wide distribution of arid and desert regions across the HTP. Thus, the previously reported BC concentrations at two remote stations of the HTP, Nam Co and Everest were adjusted to ...